EXPERIENCES OF FAMILY MEMBERS TAKING CARE OF FAMILY MEMBERS SUFFERING FROM ALZHEIMER’S DISEASE - GEVORGIANIENĖ, Violeta; PILKYTĖ, Danguolė (Socialinė teorija, empirija, politika ir praktika, 2016)
Lithuanian society is quickly aging. It is presumed that in 2030 there will be 27 perc. persons older than 60. Aging population is affected by various diseases, including Alzheimer’s disease. According to the State Mental Health Centre, almost half of the people between 85-90 years may have this disease, but only 1,5 thousand are registered officially. The problem of diagnosis lies in the symptoms of Alzheimer’s disease – they often overlap with symptoms of other illnesses and are not easily recognisable. It is found that this disease affects males more often. Alzheimer’s disease, which deteriorates all areas of a person’s functioning, is a continuous stressor, which affects the whole family system. Immediate members of a family have to make a decision related to the patient’s care. Due to the lack of specialised services for persons suffering from this disease, family members often resolve to care for the patient at home. Research (Lemme, 2003, etc.) indicates that caring for the affected family member is often considered the duty of a female member of the family. Qualitative research presented in this article is aimed at investigating specific experiences of a family looking after a person with Alzheimer’s. The data is analysed in the perspective of intergenerational solidarity (Bengston et al., 2001), which encompasses various aspects of relationships between parents and their adult children. Few types of intergenerational solidarity are identified: normative solidarity, defined by mutual expectations and values, which determines mutual duties; structural solidarity, which refers to the factors that enhance or reduce the opportunity for social interaction between parents and children; associational solidarity, which reflects intensity of communication; affectual solidarity, as a degree of positive emotions and their reciprocity; consensual solidarity, as an agreement on values, attitudes, and beliefs among family members, and, finally, functional solidarity, which addresses the quantity of help and exchange that takes place between the family members. Despite some criticism of this approach, it does allow to reveal the deficit of psychosocial resources that a family possesses, as well as to identify areas that require external support. Seven participants took part in the research. Five of them were taking care of their family member affected by Alzheimer’s, two (a social worker and a psychologist) were working with persons suffering from Alzheimer’s and their family members. Three informants took care of their mothers, one – of her father and one – of her husband. The length of care varied from two to six years. The average age of informants was 54,2 years. The average age of a family member with Alzheimer’s – 78,6 years. All ethical considerations, including information about the aim of the research, its process and length, confidentiality of data, free choice of interview time and place were taken into consideration. The research yielded the following results: decision to care about a family member at home was often caused by distrust in the official care system, but also by the so-called normative solidarity – the feeling of responsibility for the family member affected by Alzheimer’s. In the process of care, caregivers met serious psychosocial challenges that they were not always able to master independently. One of the most difficult experiences was the decline of personality of a family member affected by the disease, especially, if he or she used to be a source of support to others earlier (as in the case of a parent affected by the disease). Often participants stated the deterioration of relationships with the person and a feeling of “an end”. At the same time, the disease increased mutual interdependence, especially when the person could no longer take care of herself. From the perspective of intergenerational solidarity, this mutual dependence is often caused by affectual solidarity developed during all life. The psychologist stated that this dependence was one of the obstacles to seek psychological support, because the caregiver was reluctant to leave her mother/father at home. Interviews with experts revealed that families needed two types of support – one for the sick family member and another – for the caregiver. However, caregivers themselves did not articulated this need, denied the need for official support and were instead inclined to search for inner resources that would help them to cope with the situation (such as talking to a sister or another family member, a neighbour, etc.). From the perspective of intergenerational theory, the functional solidarity in difficult daily situations was extremely important. Only when the challenges of caring for a family member exceeded caregivers’ inner resources, family members did decide to seek external support. The need for the support “here and now”, when the problem occurs, was stressed upon. However, there are no services specifically designed for the needs of caregivers. Even social workers and other specialists don’t have sufficient knowledge about Alzheimer’s disease and needs of informal caregivers; as a result, family members lack information, psychological support and feel “invisible” to the social service system. In this situation, the functional solidarity, expressed in mutual exchange of support among extended family members was the key factor. Considering possible tensions or conflicts in the family system, such reliance solely on a family support should be considered a risk factor. Due to the limited number of participants, research results cannot be generalised, however, they reveal the urgent need to search for ways to reduce the caregivers’ stress and fatigue, to create opportunities for carers to remain in the labour market and active social life in general.